A comparative study between Antioxidant vitamin and KellgrenLawrence grading scale in knee osteoarthritis patients (Bangladesh Journal of Medical Science, 2013)
Osteoarthritis (OA) is a strongly age-related joint disorder that is defined as a gradual loss of articular cartilage. Current concepts of the pathogenic mechanisms of OA suggest that there isa shift in the homeostatic balance between the destruction and synthesis of bone and cartilage,with a net progressive destruction of these tissues. Recent studies of the biology of chondrocytes show that these cells actively produce reactive oxygen species (ROS). ROS are capable of inducing apoptotic cell death in chondrocytes, but more important, they can result in the degradation of aggrecan and collagen. Micronutrient antioxidants such as alpha- Tocopherol (Vitamin E) and Vitamin C also act to reduce the effects of ROS. A hospital based case control study was conducted in Burdwan Medical College, West Bengal, India on 76 postmenopausal women aged 4570 years suffering from Osteoarthritis (OA) of the knee joint, which was diagnosed from symptoms, clinical examinations and radiographic findings. The 151 controls were selected from the healthy persons .plasma vitamin C and serum vitamin E ware measured.. Knee joint radiographs were evaluated with the KellgrenLawrence grading scale .Furthermore both were correlated with KellgrenLawrence grading scale to find out possible association between the antioxidant vitamins and the disease progression. Results showed that there was a significant decrease in antioxidant vitamin levels in patients with knee joint osteoarthritis as compared to the controls suggests that treatment with antioxidants in the initial stages of the disease may be useful as secondary therapy. Both antioxidant vitamins showed negative correlation with KellgrenLawrence grading. Both vitamins decreased with increasing KellgrenLawrence grade. So antioxidant vitamin can be use to assess the disease severity. DOI: http://dx.doi.org/10.3329/bjms.v13i1.14046 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 30-35